(untitled) (Research, Society and Development, 2023)
Objective: to assess sleep, risk of apnea and level of sleepiness in people with Systemic Arterial Hypertension (SAH) who use UBS. Methods: clinical, observational and cross-sectional research carried out with 42 people with SAH. Data collection: Participant Profile Questionnaire, Pittsburgh Sleep Quality Index, Epworth Sleepiness Scale and Berlin Clinical Questionnaire. Results and Discussion: of the 42 participants, 24 had poor sleep (57%) or disorder (17%), 67% were at high risk for apnea, and about 31% had excessive sleepiness. When comparing Sleep Quality and Sleepiness between genders, a significant difference was evidenced for the PSQI, with worse sleep for women (p<.001). Epwoth showed no difference (p=0.808). The comparison between Sleep Quality and Sleepiness between practitioners and non-practitioners of physical activity identified a difference only for PSQI (p=0.038). Conclusion: poor or even disturbed sleep quality, high risk for apnea and excessive daytime sleepiness are present and should be further investigated in people with SAH. The sleep of women and sedentary people has worse quality.